Efecto antiinflamatorio del gel a base del extracto hidroalcoholico de las hojas Pelargonium Robertianum L. (Geranio) en ratas albinas - Samaniego Rojas, Sunny Valeria; Monzón Velázquez, Vianca Roció (Universidad Privada de Huancayo Franklin Roosevelt, 2021)
El consumo frecuente de los antinflamatorios no esteroideos (AINES) son considerados la causa principal de los efectos adversos graves de las enfermedades gastrointestinal, el Objetivo del estudio fue determinar el efecto antiinflamatorio del gel a base del extracto hidroalcoholico de las hojas Pelargonium Robertianum L. (Geranio) en ratas albinas. Metodología experimental; prospectivo y longitudinal. Resultados indicaron que en el EHHPR se identificaron alcaloides, taninos, triterpenos, esteroides, leucoantocianidinas, flavonoides y azúcares reductores, así también presentó muy buena solubilidad en metanol. Concluyéndose que el gel a base del EHHPR 3% y 5% ejerce efecto antiinflamatorio

The frequent consumption of non-steroidal anti-inflammatory drugs (NSAIDs) is considered the main cause of serious adverse effects of gastrointestinal diseases. The objective of the study was to determine the anti-inflammatory effect of the gel based on the hydroalcoholic extract of Pelargonium Robertianum L. (Geranium) leaves in albino rats. Experimental methodology; prospective and longitudinal. Results indicated that alkaloids, tannins, triterpenes, steroids, leucoanthocyanidins, flavonoids and reducing sugars were identified in the EHHPR, as well as very good solubility in methanol. It was concluded that the gel based on EHHPR 3% and 5% exerts an anti-inflammatory effect
Anti-inflammatory effect of gel based on the extract the hydroalcoholic of the leaves pelargonium robertianum l.(geranium) in albinus rats
Keywords: Efecto antiinflamatorio; Pelargonium Robertianum L; Geranio; Carragenina; https://purl.org/pe-repo/ocde/ford#3.01.05